More about learning styles (Journal of Parents and Teachers, 2026)
The article offers some reflections on the school as an institution, whose methods are not really the most suitable for learning, as children grow and develop at their own individual biological and personal pace, whilst the school expects everyone to learn the same things, at the same time and in the same way. Nowadays, there is talk of multiple intelligences, a reality that calls on schools to be a motivating environment for natural learning rather than a rigid system that leads to failure.
Keywords: school; learning process; personal development; multiple intelligences